2011
DOI: 10.1007/s11104-011-0942-4
|View full text |Cite
|
Sign up to set email alerts
|

Responses of CO2 efflux from an alpine meadow soil on the Qinghai Tibetan Plateau to multi-form and low-level N addition

Abstract: Aims To assess the effects of atmospheric N deposition on the C budget of an alpine meadow ecosystem on the Qinghai-Tibetan Plateau, it is necessary to explore the responses of soil-atmosphere carbon dioxide (CO 2 ) exchange to N addition.Methods Based on a multi-form, low-level N addition experiment, soil CO 2 effluxes were monitored weekly using the static chamber and gas chromatograph technique. Soil variables and aboveground biomass were measured monthly to examine the key driving factors of soil CO 2 effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 47 publications
5
51
0
5
Order By: Relevance
“…We did not observe a significant decrease in soil CO 2 flux at the high N treatments, suggesting that the subtropical plantation is in the early or medium stages of N saturation (Aber et al 1998). Generally, the promoting effect has a short duration (e.g., less than 1 year) and shifts to the neutral and inhibitory effects (Bowden et al 2004;Fang et al 2012). In our study, we found that each N treatment significantly increased soil CO 2 flux in the first 6 months of N addition , while the promotion was only observed at the low-NaNO 3 treatment after 1-year N addition (Fig.…”
Section: Effects Of N Levels and Forms On Soil Co 2 Fluxmentioning
confidence: 66%
See 2 more Smart Citations
“…We did not observe a significant decrease in soil CO 2 flux at the high N treatments, suggesting that the subtropical plantation is in the early or medium stages of N saturation (Aber et al 1998). Generally, the promoting effect has a short duration (e.g., less than 1 year) and shifts to the neutral and inhibitory effects (Bowden et al 2004;Fang et al 2012). In our study, we found that each N treatment significantly increased soil CO 2 flux in the first 6 months of N addition , while the promotion was only observed at the low-NaNO 3 treatment after 1-year N addition (Fig.…”
Section: Effects Of N Levels and Forms On Soil Co 2 Fluxmentioning
confidence: 66%
“…However, the effects of increased N deposition on soil CO 2 flux are high variable, including promotion (Cleveland and Townsend 2006;Contosta et al 2011), inhibition (Mo et al 2008;Janssens et al 2010), and no change (Allison et al 2008), depending on the level and the form of N addition (Fang et al 2012), on the duration of N addition (Hasselquist and Högberg 2014), and on distinct stages of N saturation (Sutton et al 2011). In addition, these studies have been conducted using a type of N fertilizer (e.g., NH 4 NO 3 or urea) (Mo et al 2008;Phillips and Podrebarac 2009), and the contrasting effects of oxidized NO 3 − and reduced NH 4 + have rarely been investigated (Lu et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidized NO 3 -and reduced NH 4 + inputs contrastingly affect soil greenhouse gas exchange fluxes. The promotion or inhibition on soil greenhouse gas fluxes are stronger from NH 4 + -N fertilizer addition than from NO 3 --N fertilizer addition (Jiang et al, 2010;Fang et al, 2012;Wang et al, 2014). Also, the responses of soil greenhouse gas fluxes to N addition dose exhibit a nonlinear curve.…”
Section: 53mentioning
confidence: 99%
“…Low dose of N addition inhibits soil CO 2 and N 2 O emissions, but promotes soil CH 4 uptake, whereas high doses of N inputs have contrary effects. Overall, these contrasting responses depend on the different stage of N saturation in terrestrial ecosystems (Fang et al, 2012. Furthermore, the environmental mechanisms driving the responses of soil greenhouse gas fluxes in the northern and southern forests of China to N enrichment are contrasting.…”
Section: 53mentioning
confidence: 99%